Liberté de grève et liberté de commerce. Le régime de la grève légale au Québec au regard de celui découlant de la législation américaine du travail - Verge, Pierre (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1988)
Although built around the same basic principles of exclusive representation of unit employees in favour of the majority union, the legislative systems regulating the collective bargaining process in Quebec and within the American federal jurisdiction present significant differences with respect to both the scope of permissible strike action and the course of a legal strike. A survey of the relevant discrepancies reveals that the legislative framework is more stringent in Quebec. The relative flexibility of the American system tends to work against the employer when one looks at the greater availability of the right to strike that it affords. This is not only the case with respect to so-called economic strikes over collective bargaining issues, but also with respect to different kinds of protest strikes. On the other hand, the American employeur seems to enjoy a relatively freer hand in taking different measures to counteract a strike, for instance, through the use of permanent replacements. A certain internal equilibrium may then be prevalent within each of the compared legal systems. The competitive situation of American and Canadian employers included within the same free trade zone is also dependent upon wider juridical and non juridical factors. As to the more pronounced degree of state intervention with respect to collective bargaining in Canada, its historical roots would tend to preserve it.